Small Yuezhi – the “vanished” Zhat tribes: Lin-Yi and Funang. (Journal of history, 2024)
The article examines the history of the kingdom of Lin-i in Southeast Asia as a result of the ethnic development of the kingdom of the Little Yuezhi, who left Southern Siberia with the ethnonym Tsat (in Kazakh Zhat). Based on the epigraphic inscription “Wo-Kan”, the influence of the Gupta (Kushan civilization) from India on China and the countries of Indochina is characterized. Also, based on eastern sources and inscriptions, an analysis of the history of the Guptas is given. These sources are of particular historical value as they reflect the early formation of the Khmer Kingdom at Prey-Nokor at the onset of Indianization brought by the Gupta Empire and are written in their script (Sanskrit), markedly similar to the Khmer cursive script used to this day. The author comes to the conclusion that part of the people of the Lesser Yuezhi, in the process of syncretization of Hinduism, Islam, which combines animists and Buddhist rituals, in addition to shamanic inclinations – «Bon», possibly brought from Siberia, became Lin-i in conjunction with Funan with the language is Jat (or Tsat) then Champoy and disappeared from the map of the earth in 1835. The “Great Yuezhi” created the Kushan kingdom, which later became the “Guptas” (Goth or Zhat) in India. The results presented in this article will be of interest to researchers in the field of Asian history and regional studies, as well as a wide range of readers whose interests are directly related to the topic raised in this study.Key words: Kingdom of Lin-i, Funan, Lesser Yuezhi, Tsat language, Guptas, inscriptions.